Instrumental neutron activation analysis of iodine levels in fourteen seaweed species from the coastal belt of Ghana. - Serfor-Armah, Y.; Nyarko, B.J.B.; Carboo, D.; Osae, E.K.; Anim-Sarpong, S.; Akaho, E.H.K. (My University, 2000)
Fourteen seaweed species were sampled from October 1997 to May 1999 along the rocky shores of Ghana, which is being washed by the Gulf of Guinea (part of the Atlantic Ocean). Instrumental neutron activation analysis (INAA) was used to measure the iodine levels in the species, with the basic aim of selecting seaweed species that are rich in iodine and hence can be used as supplement in the diet of humans. This is to help solve the problems associated with iodine deficiency disorders (IDD). The levels of iodine found in the seaweed species ranged between 55 to 804 ppm. The precision, expressed in terms of relative standard deviation, and accuracy of measurements are within ±5–10%. The results show high variability in and between species and among sampling sites. The high values of iodine concentrations in the macroalgae suggest that these marine organisms can be used as supplement in the diet of humans.
Keywords: Accuracy, Article